A psicologia nos centros de atenção psicossocial: práticas em desassossego - Bossardi, Rafaela Beal (2012)
The theme discussed in this paper emerged from a desire to deepen the knowledge about the psychological practices in the ambit of public health policies and the contemporary time. To this end, the study is presented in two complementary sections. The first uses the notions of space and time as basic categories of existence and human relationships to place psychological practices that want to be understood. Between the time of institutionalization and integration of public policy, between the performance space of the psychiatric hospital and the Center for Psychosocial Care (CAPS), psychology practice has focused on the pursuit of a fixed place that legitimizes it. In this sense, practices are focused on the bio-medical model and the logical productivity seems to contribute to the persistence of the traditional perspective of attention. Thus, the reformulation of the notion of space as "between" two fixed locations indicates the importance of professional psychologists who take the non-place that allows the flow of life's desire. The second section, in turn, carries the reflections developed in the first section to perform a research in the field. Data was collected from participation in different discussion forums on mental health, from notes in field diaries, from documents of public domain and narrative interviews with CAPS professionals. From a qualitative approach, the interviews were analyzed based on the proposal of Schütze presented by Bauer and Jovchelovitch (2002). The results of the chosen trajectory confirmed the already stated in literature, but also amazed because of the tension between progress and deviations that the consolidation of public mental health policy still finds as obstacles in their path. Given this, it points out the importance of continuing to support studies of psychological practices which can be developed between the experiential and geographic territories.